Psychological distress and emotional pain among adult attendees of a dental clinic: a case-control study - Adebayo Rasheed Erinfolami; Andrew Toyin Olagunju; Yewande Olufunmilayo Oshodi; Abiola Adelphine Akinbode; Babatunde Fadipe; Wasiu Lanre Adeyemo (Mental Illness)
We set out to carry out a case-control evaluation of psychological distress and emotional pain among adult attendees of a Nigerian dental clinic. A total of 201 subjects, made up of 101 dental patients (test group) matched with age and sex with 100 normal subjects (controls), was recruited into the study. All participants completed a designed socio-demographic questionnaire. General Health Question naire and Psyche ache Assessment Schedule were also administered to assess psychological distress based on cut-off scores ≥3 and emotional pain based on cut-off scores ≥28 respectively. The mean ages of study and control group were 33 (±12) and 36 (±13) years respectively, and both study and control groups were not significantly different in all the assessed socio-demographic parameters. Overall, 21.8% (n=22) of the subjects had psychological distress, while only 7% of the control group had psychological distress. This difference was statistically significant (P=0.003). Similarly, there was significant difference in the experience of psyche ache (unbearable psychological pain) as over a third of the dental patients (37.6%, n=38) had emotional pain, while only 13% of the controls experienced psych ache (P<0.001). In this study, the burden of psychological distress and emotional pain was many-fold in dental patients when compared with the controls.